The Structural Model of Family Performance Based on Attachment Styles with the Mediating Role of Differentiation - Hajiloo, Maryam; Goodarzi, Mahmoud; Ahmadian, Hamzeh (International Journal of Psychosocial Rehabilitation, 2020)
Family has a structure of power whereby it manifests various forms of communication. Every family has its own specific way of dealing with problems. The members of this system have a deep and multi-layered relationship with each other. Family members to a large extent also have a shared background, shared internalized perceptions, assumptions and views about the world, and shared perception of life’s goals. The aim of the present research is to compile a structural model of family performance based on the attachment styles of the mediating role of differentiation, that with a sample size of 500 couples selected by the rule of thumb from the offices of Khoy city as available from the normal (military and cultural) families of employees, that by distributing the questionnaire of attachment styles, differentiation and family performance were collected and analyzed, which according to descriptive indicators, the main variables as well as the goodness indices and the fitness of the model, the direct and indirect effects of the variables and the covariance correlation matrix were used, and the findings show that the mean of family performance evaluation in the whole sample is equal to 31.79. The highest direct effect on the structure of family performance is through differentiation being affected by 0.369. The results show that the mediating role of differentiation is effective in a positive relationship between attachment styles and family performance and can also prevent marital conflicts that reduce family performance.